Analisis Perilaku Off-task Peserta Didik Kelas VI: Studi Kasus pada Sekolah Dasar Plus Bina 45 - Fathurrahman, Adistra; Setyaningrum, Vidya (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
One of the learning behavior problems of slow learners is off-task behavior during assignments. This study aims to identify and understand the factors that influence this behavior, which often disrupts concentration and learning effectiveness. The method used was a case study of 6th grade students at SD Plus Bina 45 Pontianak. Data were collected by direct observation of students' behavior during learning, interviews and documentation. The results of the research obtained by researchers from observation and interview data found that of the 35 learners who were in the class all performed off-task behavior in the form of talking to friends, leaving class without permission, disturbing other friends, daydreaming, sleeping in class, eating and drinking, and drawing or crossing out books. Off-task behavior is caused by lack of attention from the teacher, disinterest in the subject matter, and the influence of the external environment. In addition, the study found that these behaviors often arise in response to students' physical or emotional discomfort. The findings are expected to provide insights for educators and parents on the importance of creating a conducive learning environment as well as strategies to reduce off-task behaviors, thereby increasing students' engagement in the learning process.